The Influence of Consumer Motivation on Fruit Purchase Decisions - Yessin Putri Triantika; Anis Nurhikmah; Fika Desyana Milantika; Chindy Maelani Devi; Achmad Faqih (Pusat Publikasi Nusantara, 2023)
Fruits are one type of annual horticultural plant that is commonly known to the public and consumed as additional food ingredients with good properties for body health. Fruit commodities play an important role in increasing nutritional levels in the food needed by everyone, because in fruits contain many vitamins and minerals which are important nutritional components needed by the body. This study aims to determine the influence between consumer motivation on fruit purchase decisions. The research location was carried out in Pasar Minggu, Palimanan District, Cirebon Regency from May to June 2023 with the object of research being fruit consumers with a sample of 50 respondents. The design in this study used quantitative methods with data collection using questionnaire instruments. The data used are primary data and secondary data. The data analysis used is descriptive analysis, multiple linear analysis, t test analysis, f test analysis and coefficient of determination. The results of a simple linear regression analysis produce a regression equation that is Y = 13.046 + 0.809X + e which means that every addition of 1% motivation will increase purchasing decisions by 0.809 kg and the value of the coefficient of determination of 0.517 which indicates consumer motivation affects purchasing decisions by 51.7%. The calculated F value of 53.454 is greater than the F table of 4.034, the Significance value of 0.000 is less than the Significance level of 0.050 and the calculated T value of 7.311 is greater than the T table 2.007, thus indicating the influence of consumer motivation on purchasing decisions